Two blast-resistant elite rice lines with the QTL Pi9 introgressed, ready for use in Colombia - CGIAR Research Program on Rice (2021)
Pi9 blast resistance gen was absent in LAC germplasm. It was introgressed into an elite indica background in CIAT , and this product was then delivered to FEDEARROZ and now has been used as parental donnor fro Pi9 gen in several crosses that are under evaluation.